Critical thinking and its relationship to effective teaching skills among middle school history teachers - Rasha Nima Aylan; Dr. Haider Al-Haj Al-Amin Ibrahim; Dr. Siddiq Muhammad Ahmed (Journal of College of Education, 2025)
Critical thinking is the presence of a set of skills that include the ability to think critically for history teachers, including: distinguishing between historical fact and point of view, diagnosing objectivity and bias in the historical text, forming conclusions about the historical text, evaluating historical arguments and evidence, and making logical assumptions with historical content. As for effective teaching skill, it is the ability to perform a specific work or activity related to the teacher’s professional teaching activity, whether this work or activity is during planning for teaching, during its implementation, or during its evaluation. Training and practicing the teaching skill is a basic condition for mastering it